The role of inputs of marine wrack and carrion in sandy‐beach ecosystems: a global review. (11th August 2022) - Hyndes, Glenn A.; Berdan, Emma L.; Duarte, Cristian; Dugan, Jenifer E.; Emery, Kyle A.; Hambäck, Peter A.; Henderson, Christopher J.; Hubbard, David M.; Lastra, Mariano; Mateo, Miguel A.; Olds, Andrew; Schlacher, Thomas A.
ABSTRACT: Sandy beaches are iconic interfaces that functionally link the ocean with the land via the flow of organic matter from the sea. These cross‐ecosystem fluxes often comprise uprooted seagrass and dislodged macroalgae that can form substantial accumulations of detritus, termed 'wrack', on sandy beaches. In addition, the tissue of the carcasses of marine animals that regularly wash up on beaches form a rich food source ('carrion') for a diversity of scavenging animals. Here, we provide a global review of how wrack and carrion provide spatial subsidies that shape the structure and functioning of sandy‐beach ecosystems (sandy beaches and adjacent surf zones), which typically have little in situ primary production. We also examine the spatial scaling of the influence of these processes across the broader land‐ and seascape, and identify key gaps in our knowledge to guide future research directions and priorities. Large quantities of detrital kelp and seagrass can flow into sandy‐beach ecosystems, where microbial decomposers and animals process it. The rates of wrack supply and its retention are influenced by the oceanographic processes that transport it, the geomorphology and landscape context of the recipient beaches, and the condition, life history and morphological characteristics of the macrophyte taxa that are the ultimate source of wrack. When retained in beach ecosystems, wrack often creates hotspots of microbial metabolism, secondary productivity, biodiversity, and nutrient remineralization. Nutrients are produced during wrack breakdown, and these can return to coastal waters in surface flows (swash) and aquifers discharging into the subtidal surf. Beach‐cast kelp often plays a key trophic role, being an abundant and preferred food source for mobile, semi‐aquatic invertebrates that channel imported algal matter to predatory invertebrates, fish, and birds. The role of beach‐cast marine carrion is likely to be underestimated, as it can be consumed rapidly by highly mobile scavengers (e.g. foxes, coyotes, raptors, vultures). These consumers become important vectors in transferring marine productivity inland, thereby linking marine and terrestrial ecosystems. Whilst deposits of organic matter on sandy‐beach ecosystems underpin a range of ecosystem functions and services, they can be at variance with aesthetic perceptions resulting in widespread activities, such as 'beach cleaning and grooming'. This practice diminishes the energetic base of food webs, intertidal fauna, and biodiversity. Global declines in seagrass beds and kelp forests (linked to global warming) are predicted to cause substantial reductions in the amounts of marine organic matter reaching many beach ecosystems, likely causing flow‐on effects for food webs and biodiversity. Similarly, future sea‐level rise and increased storm frequency are likely to alter profoundly the physical attributes of beaches, which in turn can change the rates at which beaches retain and process the influxes of wrack and animal carcasses. Conservation of the multi‐faceted ecosystem services that sandy beaches provide will increasingly need to encompass a greater societal appreciation and the safeguarding of ecological functions reliant on beach‐cast organic matter on innumerable ocean shores worldwide.